The moral of the story : an anthology of ethics through literature - Singer, Peter, 1946-; Singer, Renata (Malden, MA : Blackwell Pub., 2005)
Presents a collection of short fiction and selections from literature emphasizing ethics and moral judgment, and includes selections from James Baldwin, William Shakespeare, Nick Hornby, Douglas Adams, Fyodor Dostoyevsky, and many others.
Personal moral issues -- Who am I? -- Duties to kin -- Love, marriage and sex -- Abortion, euthanasia, and suicide -- The community and beyond -- Work -- What do we owe to our country, compatriots, and strangers? -- Ethics and politics -- Racism and sexism -- War -- Animals and the environment -- Duties to God -- New life forms -- Reflecting on ethics -- The nature of ethics -- Rules, rights, duties, and the greater good -- Ultimate values -- Issues.
Includes bibliographical references (p. 610-616).
Adult
Keywords: Ethics -- Literary collections; Ethics -- Literary collections